2014
DOI: 10.1519/jsc.0b013e318291b713
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance Profile of Handball Players Is Related to Playing Position and Playing Class

Abstract: The purpose of the study was to compare anthropometric data and physical performance characteristics between different playing positions in professional team handball. Furthermore, a comparison between performance profiles of first and second division players was made. Thirty-four male professional handball players were recruited. Measurement of heart rates (HRs) during official games anthropometric data, sprint ability, jumping performance, throwing velocity, and endurance performance were determined and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
74
6
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 16 publications
14
74
6
7
Order By: Relevance
“…Establecer un perfil de alto rendimiento especí-fico para cada deporte es uno de ellos para poder realizar una buena detección de talentos y alcanzar el mayor rendimiento posible (Claessens et al, 1999;Di Cagno et al, 2009;Slezynski & Swiat, 1997;Rodríguez et al, 2014). Dentro de la especialización en cada deporte también es necesario determinar patrones morfológicos más aptos para un determinado puesto o rol (Krüger et al, 2014;Slezynski & Swiat).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Establecer un perfil de alto rendimiento especí-fico para cada deporte es uno de ellos para poder realizar una buena detección de talentos y alcanzar el mayor rendimiento posible (Claessens et al, 1999;Di Cagno et al, 2009;Slezynski & Swiat, 1997;Rodríguez et al, 2014). Dentro de la especialización en cada deporte también es necesario determinar patrones morfológicos más aptos para un determinado puesto o rol (Krüger et al, 2014;Slezynski & Swiat).…”
Section: Introductionunclassified
“…Establecer un perfil de alto rendimiento especí-fico para cada deporte es uno de ellos para poder realizar una buena detección de talentos y alcanzar el mayor rendimiento posible (Claessens et al, 1999;Di Cagno et al, 2009;Slezynski & Swiat, 1997;Rodríguez et al, 2014). Dentro de la especialización en cada deporte también es necesario determinar patrones morfológicos más aptos para un determinado puesto o rol (Krüger et al, 2014;Slezynski & Swiat).Por otro lado, Classens et al (1996), establecieron que el perfil morfológico en gimnasia se encuentra relacionado con la tasa de lesión, por lo que los estudios antropométricos permiten realizar una mejor prevención de lesiones.La composición corporal y los índices de proporcionalidad son parámetros muy estudiados en ciertas disciplinas gimnásticas pertenecientes a la Federación Internacional de Gimnasia (FIG) como la Gimnasia Artística Masculina y Femenina (GAM y GAF), Gimnasia Rítmica (GR), Trampolín y Gimnasia Aeróbica (GAer) donde existe una mayor evidencia científica referente a la tipología morfológica (Claessens et al, 1991(Claessens et al, , 1999Bester & Coetzee, 2010;Díaz et al, 2008;Ávila-Carvalho et al, 2012;Klentrou & Plyley, 2003; Lopez-Benedicto et al, 1991;Quintero et al, 2011;Vernetta et al, 2011;Gómez-Landero et al, 2004López Bedoya et al, 1999;Mineva, 2011) No obstante en Gimnasia Acrobática (GA), al ser la última disciplina gimnástica integrada en la FIG en 1999, los estudios se encuentran en las primeras etapas de desarrollo, por lo que no existen muchos trabajos científicos, siendo el de Slezynski & Swiat uno de los realizados sobre el perfil antropométrico de gimnastas de GA de clase mundial y gimnastas polacos.La GA es una disciplina que está incrementando tanto el nivel como en participación. Se trata de un deporte sociomotriz, donde existe siempre la presencia de uno o varios compañeros que sincronizan sus acciones en un espacio estable reglado (12x12 m), para conseguir la realización de lanzamientos, figuras y pirámides humanas (Vernetta et al, 2008).…”
unclassified
“…Additionally, our findings could have been even more meaningful, if additional age groups or further important anthropometric characteristics, like segmental specific measures for body fat and fat-free mass (47), as well as physical capacities, such as ball throwing velocity (12), jumps involving opening steps (48), repeatedsprint ability (21), or performance circuits (1), would have also been tested. However, it must be reflected that our data were obtained from unique populations.…”
Section: Discussionmentioning
confidence: 98%
“…4). In this context, previous studies have focused on the body height, mass, fat, and fat-free mass (10,14) as well as 30 m speed (12,13) and COD (15,16), squat jump (SJ) and counter movement jump (CMJ) (14,17), one repetition maximum (1RM) bench press (18,19), core strengthendurance (16,17), and intermittent shuttle running (20,21) performance of handball players from various backgrounds. While there exists many studies that have investigated such variables in adults (1, 4, 8, 10-12, 17-19, 21-23), there are less studies in juniors (3,16,20,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…These studies are often contradicting and inconclusive regarding the role and importance of different physical related to the playing level and position in elite ball sports, especially in handball [27]. Some studies concluded differences in variables such as the velocity of a throw [28][29][30][31], dynamical characteristics and the height of the jumps [32], absolute values of bench press and half squat [29]. While other researchers such as [29,33] suggested no significant differences in sprinting and jumping ability, in bench pressing or squatting.…”
Section: Analysis Of Physical Performance Profile In Youth and Juniormentioning
confidence: 99%